1992
DOI: 10.1002/j.1556-6676.1992.tb02194.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Wellness: The Integration of Career Identity and Personal Identity

Abstract: Historically, career and vocational counseling have served as cornerstones to the counseling profession. Still, there are several survey studies that indicate that interest in career counseling among counseling professionals has eroded. Conversely, there has been an overwhelming response from counselors to the idea of wellness. The intent of this article is to encourage practicing counselors and researchers to consider career development as a key ingredient in the conceptualization of wellness. Furthermore, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
1
15
0
3
Order By: Relevance
“…Findings of this study are consistent with the findings of previous studies (e.g., Anderson & Niles, 1995;Dorn, 1992;Imbimbo, 1994;Krumboltz, 1993;Manuele-Adkins, 1992) which showed that counseling students hold misconceptions regarding interrelationships between career and personal counseling. Participants with no previous career counseling experience lacked a framework for understanding the purpose or value of career counseling.…”
Section: Discussionsupporting
confidence: 94%
“…Findings of this study are consistent with the findings of previous studies (e.g., Anderson & Niles, 1995;Dorn, 1992;Imbimbo, 1994;Krumboltz, 1993;Manuele-Adkins, 1992) which showed that counseling students hold misconceptions regarding interrelationships between career and personal counseling. Participants with no previous career counseling experience lacked a framework for understanding the purpose or value of career counseling.…”
Section: Discussionsupporting
confidence: 94%
“…F. J. Dorn (1992) examines professional career due to the nature of identification of a person in the career and beyond, examining the influence of social and psychological factors on the choice of education and profession. M. Woodcock (2002), and D. Francis, studying professional career, divide it into stages associated with age-related changes of human rights.…”
Section: Discussionmentioning
confidence: 99%
“…L. Dale (2004) teigia, kad organizacijos kultūra, netiesiogiai įtakoja asmeninius asmens pasirinkimus, susijusius su sveikata ir gerove. Todėl kuriant darbuotojų gerovės organizacijoje stiprinimo programas svarbus yra asmens ir organizacijos vertybių atitikimas (Cennamo, Gardner, 2008), vertybiniai įsitikinimai apie sveikatą (Conrad, 1994), sveikatai palankaus gyvenimo būdo vertybių integracija į darbuotojo vaidmenį, identitetą (Dorn, 1992). Socialinis palaikymas darbe taip pat yra būtina palankios darbo aplinkos sąlyga (Pascual ir kt.…”
Section: Pozityvių Psichologinių Bei Socialinių Veiksnių Stiprinančiunclassified